Exploring the Mediating Role of Brand Attachment in the Relationship between Mobile Banking Service Quality and eWOM - Umar, Nurfadillah Ramadhani; Rufaidah, Popy (Universitas Proklamasi 45, 2025)
In today's digital era, the quality of mobile banking services is a crucial factor in the banking industry. This study evaluates how mobile banking service quality affects bank customers' brand attachment and electronic word of mouth (eWOM). The study employed an online survey and analyzed the data using a statistical technique called Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that value-added features, security and privacy, and interactivity positively affect brand attachment. In addition, value-added features also have a positive effect on eWOM. Brand attachment has a positive relationship with eWOM and mediates security/privacy, value-added features, and interactivity with eWOM.